Linguistic and Cultural Differences in Information Categorization and their Impact on Website Use - Kralisch, Anett; Wee, Alvin Yeo (2006)
The Internet is increasingly used as a medium for providing medical information. Nevertheless, whether the World Wide Web is favoured over other information sources depends to a large extent on how easily the sought information can be found. Therefore, this paper investigates the impact of culture, language and medical knowledge on users’ preferences of information categorization and on the evaluation and use of search cues and search options. Results from a laboratory experiment with 141 Malaysian, British, Russian, and German test subjects revealed significant differences but also commonalities between these groups. As a consequence of their limited medical knowledge, all groups exhibited a preference for visual cues over verbal cues. Outcomes suggest furthermore that culture mainly influences the users’ preferences in information categorization as well as their attitudes and using behaviour, whereas language predominantly affects the users’ beliefs about ease of use and usefulness.